2021
DOI: 10.3389/fcell.2021.641162
|View full text |Cite
|
Sign up to set email alerts
|

Role of OSCAR Signaling in Osteoclastogenesis and Bone Disease

Abstract: Formation of mature bone-resorbing cells through osteoclastogenesis is required for the continuous remodeling and repair of bone tissue. In aging and disease this process may become aberrant, resulting in excessive bone degradation and fragility fractures. Interaction of receptor-activator of nuclear factor-κB (RANK) with its ligand RANKL activates the main signaling pathway for osteoclastogenesis. However, compelling evidence indicates that this pathway may not be sufficient for the production of mature osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 124 publications
(246 reference statements)
2
34
0
1
Order By: Relevance
“…Moreover, qRT-PCR was also used to confirm the expression of TRAP when cells were cultured on Fmoc-FF/S/RGD with incorporated Hap. Indeed, since the OC-commitment it is known to begin around days 2–3 [5] , we compared the expression of TRAP at day 7 with that at day 3 and we successfully demonstrated that there was a significant increased expression of TRAP at day 7 ( Fig. 6 E ), confirming the OC-differentiation of Raw 264.7 cells cultured on Fmoc-FF/S/RGD with incorporated Hap.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Moreover, qRT-PCR was also used to confirm the expression of TRAP when cells were cultured on Fmoc-FF/S/RGD with incorporated Hap. Indeed, since the OC-commitment it is known to begin around days 2–3 [5] , we compared the expression of TRAP at day 7 with that at day 3 and we successfully demonstrated that there was a significant increased expression of TRAP at day 7 ( Fig. 6 E ), confirming the OC-differentiation of Raw 264.7 cells cultured on Fmoc-FF/S/RGD with incorporated Hap.…”
Section: Resultsmentioning
confidence: 53%
“…Bone is a highly dynamic and hierarchically organised organ, consisting of a complex network of cells embedded in a 3D structure of organic-inorganic nanocomposite, which confers remarkable mechanical performance, including high strength and fracture toughness [ 1 , 2 ]. Bone is constantly self-renewing through a finely regulated balance of two processes: osteoclastogenesis, through bone-resorbing osteoclasts (OCs), and osteoblastogenesis through bone-forming osteoblasts (OBs) [3] , [4] , [5] . Disruption of the equilibrium between these processes can cause bone defects or may lead to increased risk of bone fractures [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoclast-associated receptor (OSCAR) is another collagenbinding receptor, which is expressed in osteoclasts in mice, and in monocytes, macrophages, dendritic cells, and osteoclasts in humans (148)(149)(150). It is a member of the leukocyte receptor complex that associates with FcRg, and through FcRg-signaling OSCAR is critical for osteoclastogenesis (150,151).…”
Section: Collagen-receptors Expressed By Macrophagesmentioning
confidence: 99%
“…Роль мембранного белка Th17-лимфоцитов RANKL в патогенезе псориатического артрита состоит в его способности связываться с рецептором-активатором ядерного фактора-kB (RANK) на поверхности моноцитов/макрофагов субхондральной части кости и стимулировать их дифференцировку в остеокласты [4,13]. Кроме того, присутствующий на поверхности моноцитов остеокласт-ассоциированный рецептор (OSCAR) в присутствии TNF-α потенцирует действие RANKL, тем самым усиливая остеокластогенез [14]. Активированные остеокласты начинают секретировать ферменты деградации костного матрикса -тартрат-резистентную кислую фосфатазу (TRAP), матриксную металлопротеиназу 9 (MMP9) и катепсин К (CatK), которые подвергают резорбции минерализованную кость.…”
unclassified